1984
DOI: 10.1007/bf00542141
|View full text |Cite
|
Sign up to set email alerts
|

Binding of piroxicam to synovial fluid and plasma proteins in patients with rheumatoid arthritis

Abstract: The protein binding of piroxicam in synovial fluid and plasma from patients with rheumatoid arthritis was studied in vitro by equilibrium dialysis. The binding parameters were calculated from the experimental data with the Scatchard model, assuming binding to two classes of sites. Each plasma sample was diluted to an albumin concentration equal to that of synovial fluid from the same patient. The association constants for primary and secondary binding sites in the concentration range of piroxicam 4.5-90 X 10(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In (Rosenthal et al, 1964;Soren, 1979;Trnavska & Trnavsky, 1980) and ibuprofen (Whitlam et al, 1981) in SF than in the corresponding plasma. It has been suggested that the lower total drug concentrations in SF than in plasma is due to lower protein binding in SF.…”
Section: Resultsmentioning
confidence: 99%
“…In (Rosenthal et al, 1964;Soren, 1979;Trnavska & Trnavsky, 1980) and ibuprofen (Whitlam et al, 1981) in SF than in the corresponding plasma. It has been suggested that the lower total drug concentrations in SF than in plasma is due to lower protein binding in SF.…”
Section: Resultsmentioning
confidence: 99%
“…Since only the free drug is available to diffuse across the endothelium and other biological barriers and to produce pharmacological effect at the receptor sites in extra vas- Rosen (1970) Abbreviations: P = human plasma; A = human serum albumin; S = human serum; ED = equilibrium dialysis; FP = fluorescence probe; UF = ultrafiltration; NA = not available. Ayres et al (1977); Brogden et al (1981); Rogers et al (1981); Verbeeck et al (1983); Windholz (1983); Trnavska et al (1984); Physician's Desk Reference (1986) cular tissues as has been demonstrated explicitly for sulphonamides (Anton 1960) and other antibiotics (Kunin et al 1959(Kunin et al , 1973, phenytoin (diphenylhydantoin) [Booker & Darcey 1973;, warfarin propranolol (McDevitt et al 1976), it is more informative to express the protein binding of highly bound drugs such as NSAIDs in terms of their unbound fraction. For example, while a decrease in fraction bound from 0.99 to 0.98 may appear trivial at first sight, closer investigation shows this change represents a doubling of free fraction from 0.01 to 0.02 which may be clinically important.…”
Section: Basic Conceptsmentioning
confidence: 95%
“…The binding of piroxicam to proteins in plasma and synovial fluid was studied by Trnavska et al (1984). The binding parameters (association constants and numbers of binding sites) in the 2 fluids were similar at a given (adjusted) albumin concentration from a given patient.…”
Section: Piroxicammentioning
confidence: 99%